Sanctions and Civil Conflict - Gershenson, Dmitry (Washington, D.C. : International Monetary Fund, 2001)
Using a formal general equilibrium framework, this paper analyzes how sanctions imposed on the contestants in civil conflict affect the welfare of these contestants and the allocation of resources to conflict. It is shown that weak sanctions can hurt the contestant they are supposed to help, while strong sanctions augment the expected welfare of their intended beneficiaries. Moreover, sanctions are more likely to be successful if the contestant who is subject to sanctions can expect to derive a positive income in case of compliance. The likelihood of success rises as this income increases.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet